Kryzys, droga do upadłości - Gurgul, Stanisław (Crisis, the Way to Insolvency, 2006)
Crisis is an inseparable part of human living and doing. It comes like a wave and one should be especially alert at the time of the best prosperity. The saying of Schopenhauer (who was ! philosopher) „How unhappy I'm that I'm so happy" is its best explanation. A reason of irreversible crises in a company resulting in its insolvency is the wrong attitude of management, which allows to form a pathological behaviour in the internal and external sphere of the company, it does not diagnose the pathological relations and it does not apply the appropriate measures. A well diagnosed crisis is a beginning of the end of the company resulting in its natural liquidation or insolvency or it can be the beginning of the new prosperity. Anyway the diagnosed crisis is a turning point and it only depends on the management base which way will be chosen and accomplished.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 265-274